2018
DOI: 10.1007/s11934-018-0802-3
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in the Aging Male

Abstract: Contemporary evidence confirms that aged men have worse semen parameters, including overall negative changes in sperm genetics. Reproductive outcomes with unassisted pregnancy tend to be worse with older fathers. While most current studies of assisted pregnancy do show a negative effect of paternal age, there are some conflicting results. Studies continue to show an overall increased risk of health problems, particularly neuropsychiatric conditions, in the offspring of older men. While men can often maintain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 87 publications
3
42
1
4
Order By: Relevance
“…The semen analysis seems to be crucial for assessing the fertility potential of males. The comparisons of semen parameters of younger and older men in individual studies demonstrated inconsistent findings, while meta-analyses proved that age has a negative impact on semen quality, including volume, morphology, and motility (Mazur and Lipshultz, 2018). The present study showed that study participants with higher motility were significantly younger than those with lower motility.…”
Section: Discussioncontrasting
confidence: 50%
“…The semen analysis seems to be crucial for assessing the fertility potential of males. The comparisons of semen parameters of younger and older men in individual studies demonstrated inconsistent findings, while meta-analyses proved that age has a negative impact on semen quality, including volume, morphology, and motility (Mazur and Lipshultz, 2018). The present study showed that study participants with higher motility were significantly younger than those with lower motility.…”
Section: Discussioncontrasting
confidence: 50%
“…Ageing or other diseases have a negative influence on spermatogenic function and fertility (Cardona Maya, Berdugo, & Cadavid Jaramillo, ; Mazur & Lipshultz, ; Rybar, Kopecka, Prinosilova, Markova, & Rubes, ; Sekhavat & Moein, ; Varshini et al, ). In this study, we found that in elderly human testes, spermatogenic function declines were characterised by histological atrophic lesions and thin seminiferous epithelium, lower Johnsen's scores and decreased expression of spermatogenic cells markers, including SSC (PLZF + ), differentiating spermatogonia (C‐kit + ), spermatocyte (PIWIL1 + ) and spermatid (SMAD3 + ) (Fayomi & Orwig, ; Hermann et al, ; Sauer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Women age is a major risk factor (Fritz & Jindal, ; Shirasuna & Iwata, ), with fertility even after in vitro fertilisation (IVF) dropping below 30% already by 35 years of age (Q‐IVF, ). Male subfertility at similar age intervals is thought to be predisposed/caused by several factors all leading to low sperm count, sperm dysfunction or both (Levine et al, ; Mazur & Lipshultz, ).…”
Section: Introductionmentioning
confidence: 99%